IDENTIFIKASI KESALAHAN MAHASISWA DALAM MELAKSANAKAN PRAKTIKUM PADA MATAKULIAH KONSEP IPA 2 DI PRODI PGSD FIP IKIP PGRI MADIUN - Edy Riyanto (Universitas PGRI Madiun, 2012)
This study aims to identify kinds of mistake by students, and those contributing most in carrying out the practicum in the class of Konsep IPA 2 second term in the academic year of 2011/2012. The subjects are those attending the class as many as 40. Data were collected through an observation focusing on the types of mistakes done by the subjects while they were doing their practicum. The mistakes observed cover mistake of tools, the tool positions, arranging the tools, determining the units, the scales, and the zero point. Results show mistakes of arranging the tools reaching 60%, of parallax and determining the scale amounting 50%, on determining the zero point amounting 35%, on positions 27.5%, on the units 30%, on tools 17.5%, and on figures 12.5%. The major mistakes done by the subject are on arranging the tools.